1975
DOI: 10.1002/pssb.2220710143
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Absorption edge of In1–xGaxP Mixed Crystals Studied by Wavelength Modulation

Abstract: The advantages of the wavelength-modulation technique (1) a r e used here to in-Ga P mixed crystals and vestigate the weak structures in the indirect edge of In to observe the direct-indirect transition directly ~ because the corresponding x-value

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…the E,, E, + A, energies were taken from the minima of the DR spectra; a more detailed analysis gave only a negligible correction to the energies determined in this way. The DA spectra were evaluated as described in [14], i.e. the threshold energies were taken directly from the da/dE curves at the 9/10 amplitude of the maximum signal on its low-energy wing.…”
Section: Analpis Of Spectramentioning
confidence: 99%
“…the E,, E, + A, energies were taken from the minima of the DR spectra; a more detailed analysis gave only a negligible correction to the energies determined in this way. The DA spectra were evaluated as described in [14], i.e. the threshold energies were taken directly from the da/dE curves at the 9/10 amplitude of the maximum signal on its low-energy wing.…”
Section: Analpis Of Spectramentioning
confidence: 99%
“…This system has been shown to exhibit zero-phonon absorption and emission even in the indirect band-gap region with small amount of In (< 10%). [9,10] It is also well known to exhibit spontaneous ordering when grown by MOCVD.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the CBM being X-like at x = 0.80, the coupling with the Γ-like state does yield a finite Γ component ~ 0.5 %, which is sufficient to produce the zero-phonon absorption or emission at the X-like fundamental bandgap. [9,10] It is worth mentioning that because of the high degeneracy of the VB, it is found that at x = 0.50 the spin-orbit split off band has only ~ 45% of the Γ component, even though being merely ~ 100 meV below the VBM, which might be reflected in the weakness of the spin-orbit feature in absorption and modulation spectra for samples with x ~ 0.5. [21] Another important finding is that there is a strong inter-valley mixing among the degenerate critical points k 0 's in the VCA, even in the case they are the CBM and have a high overall purity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations